100 Franklin Street, ca. 1910-20 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northeast of the left side of Franklin Street from Arch Street toward Congress Street. The large, light-colored stone building is the Boston Safe Deposit and Trust building at 100 Franklin Street. In the distance is a sign affixed to the roof of 181 Franklin Street for McKenney and Waterbury. Electric lines and railway tracks run down cobblestoned Franklin Street. A horse-drawn vehicle waits outside of the Boston Safe Deposit building. 7 3/4 x 7 1/2 Photographs